Overview of “Race, class, and state crime” - Shank, Gregory (Social justice, 2000)
Part of a special section on race, class, and state crime. The writer introduces the articles in this special section. He outlines the topics addressed in each: the shooting of Amadou Diallo and the issue of excessive police violence; the political awakening of blacks and Latinos in New York City; the ideological-political conflict in the U.S. that is symptomatic of the interminable crisis of liberal democracy; a case study of drug offense trials in a London Crown Court; how criminology can remedy its neglect of state crime; states in transition from terror-based structures to more liberal ones in South Africa and Central America; the genocidal state structures of terror in rural Maya villages in Guatemala; anticolonial struggles in the postindependent peripheral nation-states of Ethiopia and Sudan; and how the legal model and mediation model may undermine the victim's power to act in cases of domestic violence against women.